2020
DOI: 10.21037/hbsn-20-446
|View full text |Cite
|
Sign up to set email alerts
|

International expert consensus on laparoscopic pancreaticoduodenectomy*

Abstract: Importance: While laparoscopic pancreaticoduodenectomy (LPD) is being adopted with increasing enthusiasm worldwide, it is still challenging for both technical and anatomical reasons. Currently, there is no consensus on the technical standards for LPD.Objective: The aim of this consensus statement is to guide the continued safe progression and adoption of LPD.Evidence Review: An international panel of experts was selected based on their clinical and scientific expertise in laparoscopic and open pancreaticoduode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 136 publications
(209 reference statements)
2
43
0
Order By: Relevance
“…The surgeons who performed MIPD meet the requirements by international expert consensus on laparoscopic pancreatoduodenectomy 16 (high‐volume center and experience of >200 OPD cases before starting MIPD). The patients who had the possibility of undergoing “standard PD” as recommended by the International Study Group on Pancreatic Surgery (ISGPS) underwent MIPD 17 .…”
Section: Methodsmentioning
confidence: 99%
“…The surgeons who performed MIPD meet the requirements by international expert consensus on laparoscopic pancreatoduodenectomy 16 (high‐volume center and experience of >200 OPD cases before starting MIPD). The patients who had the possibility of undergoing “standard PD” as recommended by the International Study Group on Pancreatic Surgery (ISGPS) underwent MIPD 17 .…”
Section: Methodsmentioning
confidence: 99%
“…However, a surgeon needs to take a lot of time and effort to achieve the proficiency in laparoscopic pancreatic surgery [ 24 , 25 ]. Dissection of the main blood vessels is a key step for pancreatic surgery [ 26 ]. In the current study, we tried to use advanced technology to provide an effective method to accurately locate the main blood vessels to shorten the operation time, reduce the degree of technical difficulty and accelerate the learning curve of laparoscopic pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An international consensus statement on robotic pancreatic surgery showed that robotic pancreatic surgery is safe and feasible compared to open pancreatic surgery [ 89 ]. Another international expert consensus on laparoscopic pancreaticoduodenectomy (PD) also showed that laparoscopic pancreaticoduodenectomy was safe and effective for experienced surgeons [ 90 ]. Furthermore, a current network meta-analysis indicated that laparoscopic PD and robotic PD had a reduced length of hospital stay, operative bleeding and overall complications while on the other hand achieving a similar number of retrieved lymph nodes, tumor-free resection margins, clinically relevant postoperative pancreatic fistula, severe postoperative complications [ 91 ].…”
Section: Surgerymentioning
confidence: 99%